Isolated perforation of the gallbladder due to blunt trauma - Kazez, A.; Serhatlioglu, S.; Saglam, M.; Demirbag, M.; Ozturk, C. (My University, 1997)
The gallbladder is a well-protected organ, and it's perforation due to blunt abdominal trauma is rarely encountered. The diagnosis is frequently made in laparotomy for associated visceral injury. Isolated traumatic perforation is expected in the presence of previous history of gallbladder disease in adults, but it is very uncommon in children. Herein we report a 9- year-old male patient with isolated gallbladder perforation inorder to demonstrate difficulties in its' diagnosis.
Kunt travmaya bagli izole safra kesesi perforasyonu
Keywords: Abdominal trauma; Bile ducts; Gallbladder